Effects of the Novel Lacticaseibacillus paracasei K-68 Inoculant on Nutrient Content, Fermentation, and Microbial Dynamics Changes in Dacheongok Corn Silage - Ilavenil Soundharrajan; Chang-Woo Min; Jeong Sung Jung; Ki Choon Choi (Fermentation, 2025)
This study investigated the role of Lacticaseibacillus paracasei K-68 (LABK) and cocktail LAB (LABC) as silage inoculants to enhance corn silage fermentation quality and microbial stability. Silage spoilage is primarily caused by undesirable microbes such as Clostridium, Klebsiella, yeasts, and molds. The isolated LAB strain K-68 exhibited strong antibacterial and antifungal activity, particularly against spoilage organisms, and was identified as L. paracasei. Experimental silages inoculated with LABK or a LABC significantly improved fermentation profiles, with reduced pH and increased lactic acid levels. Microbial counts revealed that LAB-inoculated silages had higher LAB counts and significantly reduced yeast and mold populations. Furthermore, there were no significant differences in acetic acid, isobutyric acid, and propionic acid levels. High-throughput sequencing confirmed that LABK-treated silage was dominated by Lacticaseibacillus paracasei, whereas LABC-treated silage supported more diverse microbiota, including Pediococcus pentosaceus, Lacrimispora xylanolytica, and Levilactobacillus brevis. Both treatments suppressed spoilage-associated genera such as Clostridium and Klebsiella. Furthermore, correlation analysis showed that Lacticaseibacillus abundance was positively associated with lactic acid production and negatively correlated with pH and yeast levels. L. paracasei K-68 is a promising bio-inoculant for corn silage production since it promotes beneficial microbial dominance and suppresses spoilage organisms better than cocktail LAB.